Manajemen Pendidikan Islam Pada Masa Turki Usmani - Safaruddin Satar; Muhammad Syaifuddin2 (Hikamatzu | Journal of Multidisciplinary, 2024)
The purpose of this discussion paper is to determine the historical development of Islamic education in the Ottoman period, which was established by the Children of Uthman, who stood more than a century of rule 36 people led by the sultan, at the time of the journey, the pattern of Islamic education is not independent of cultural setting and the conditions at that time. At the beginning of its establishment, Islamic education in the Ottoman Empire had experienced stagnation in education, so that people experience boredom and frustration, with many of the people kefrustasiannya studying Ottoman terekat growing at that time. The congregation is growing and the Al-Al-Mulawy bektasy. In the early leadership of Sultan Mahmud II, started the reform in various fields, including education, because education will have a huge influence for the kingdom. Updates are performed, not only in institutions but in the course curriculum and methods. So with these changes many students are sent to Francis to broaden your horizons, so the emergence of new ideas for the development of education in the Ottoman. The method used in this study, a qualitative descriptive, the authors reveal the facts of history that occurred during the Ottoman dynasty, through literature review, then dikatagorisasi and dikonsepsi into education, so that could be used as reference and insight in the development of Islamic education